Does job loss cause ill health? - Martin Salm (Institute for the Study of Labor (IZA), 2009)
This study estimates the effect of job loss on health for near elderly employees based on longitudinal data from the Health and Retirement Study. Previous studies find a strong negative correlation between unemployment and health. To control for possible reverse causality, this study focuses on people who were laid off for an exogenous reason - the closure of their previous employers' business. I find that the unemployed are in worse health than employees, and that health reasons are a common cause of job termination. In contrast, I find no causal effect of exogenous job loss on various measures of physical and mental health. This suggests that the inferior health of the unemployed compared to the employed could be explained by reverse causality.
urn:nbn:de:101:1-20090513459
Keywords: I12; J63; 330; Job displacement; health; unemployment; Arbeitslosigkeit; Gesundheit; Kündigung; USA